2019
DOI: 10.3390/en12244658
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Operation of Critical Peak Pricing for an Energy Retailer Considering Balancing Costs

Abstract: Recently, there have been frequent fluctuations in the wholesale prices of electricity following the increased penetration of renewable energy sources. Therefore, retailers face price risks caused by differences between wholesale prices and retail rates. As a hedging against price risk, retailers can utilize critical peak pricing (CPP) in a price-based program. This study proposes a novel multi-stage stochastic programming (MSSP) model for a retailer with self-generation photovoltaic facility to optimize both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A case study conducted in [105] showed that residential consumers exhibit a positive effect of demand response in time of CPP event, resulting in a reduction of power consumption. Several advantages of CPP include being easily implemented because it is based on the rate structure of TOU and additionally can enhance the responsiveness of the customer's price by imposing an extremely high rate during critical peak periods [106].…”
Section: ) Critical Peak Pricing (Cpp)mentioning
confidence: 99%
“…A case study conducted in [105] showed that residential consumers exhibit a positive effect of demand response in time of CPP event, resulting in a reduction of power consumption. Several advantages of CPP include being easily implemented because it is based on the rate structure of TOU and additionally can enhance the responsiveness of the customer's price by imposing an extremely high rate during critical peak periods [106].…”
Section: ) Critical Peak Pricing (Cpp)mentioning
confidence: 99%
“…As a result, the critical peak pricing (CPP) tariff needs to include a forecaster of the critical events and a decision mechanism to set the critical price. 61 Furthermore, since critical events are restricted to a certain number of hours, yearly or monthly, consequently the suppliers should sensibly decide when to recognize a critical event in order to maximize revenue. It is also worth to mention that the CPP tariff may reach five times higher than the normal tariff; however, this technique of peak load reduction illustrated a considerable effectiveness in North America.…”
Section: Critical Peak Pricingmentioning
confidence: 99%
“…The methodology developed comprises of several steps, as shown in Figure 25. Leaf Community is collected, organised and made remotely available through the MyLeaf platform [33]. In this case, the MyLeaf platform is used to collect data of ambient temperature, irradiance and power demand of the buildings considered in the analysis.…”
Section: Infrastructure and Methodsmentioning
confidence: 99%
“…Demand response is otherwise classified into (i) incentive-based, including direct load control, interruptible/curtailable rates, emergency DR, capacity market programs, and demand bidding programs, and (ii) time-based, such as time of use (ToU) rates, critical peak pricing (CPP), and real-time pricing (RTP). In CPP, a high rate is imposed on the customer in the case of critical events of high wholesale market prices [33]. In RTP, end customers are forwarded wholesale market prices a day or an hour before energy delivery.…”
Section: Demand Response and Smart Gridsmentioning
confidence: 99%